2011
DOI: 10.1093/ecam/neq065
|View full text |Cite
|
Sign up to set email alerts
|

Phytomedicinal Role of Pithecellobium dulce against CCl4‐mediated Hepatic Oxidative Impairments and Necrotic Cell Death

Abstract: Present study investigates the beneficial role of the aqueous extract of the fruits of Pithecellobium dulce (AEPD) against carbon tetrachloride (CCl4)-induced hepatic injury using a murine model. AEPD has been found to possess free radical (DPPH, hydroxyl and superoxide) scavenging activity in cell-free system. CCl4 exposure increased the activities of various serum maker enzymes and intracellular reactive oxygen species (ROS) production. In line with these findings, we also observed that CCl4 intoxication inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
19
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 54 publications
3
19
2
Order By: Relevance
“…Becker et al [37] stated that elevated activities of these enzymes are indicative of cellular leakage and loss of the functional integrity of liver cell membrane. The elevation of plasma enzymes concentration is generally regarded as one of the sensitive markers of hepatic damage [38]. In our study, CCl 4 was found to cause significant increases in plasma AST, ALT and GGT levels compared to control (p < 0.001).…”
Section: Discussionsupporting
confidence: 52%
“…Becker et al [37] stated that elevated activities of these enzymes are indicative of cellular leakage and loss of the functional integrity of liver cell membrane. The elevation of plasma enzymes concentration is generally regarded as one of the sensitive markers of hepatic damage [38]. In our study, CCl 4 was found to cause significant increases in plasma AST, ALT and GGT levels compared to control (p < 0.001).…”
Section: Discussionsupporting
confidence: 52%
“…30 Tissue homogenates were filtered through 4 layers of muslin cloth and centrifuged at 10 000 g for 20 min at 4 °C. ROS was estimated using de-esterified 2,7-dichlorofluorescein (DCFH) obtained from DCFH-DA by the hydrolysis in NaOH.…”
Section: Quantification Of Reactive Oxygen Species (Ros) In Tissue Homentioning
confidence: 99%
“…14 Present investigations aim at understanding the possible correlation among the various phases of seed development, generation, and enzymatic scavenging of ROS during these phases, activation of protein kinase C, and its modulation by calcium. In this context, qualitative and quantitative analysis of major ROS scavenging enzymes, namely superoxide dismutase (SOD), peroxidase (POD), and glutathione reductase (GR), has been undertaken at 3 stages of sunflower seed development (20,30, and 40 d after anthesis). Modulation of the activity of these enzymes with seed development has been examined for a possible correlation with calcium-stimulated protein kinase C (PKC) activity.…”
mentioning
confidence: 99%
“…Benth. Chaudhary and Taparia (2007) Hepatoprotective (Manna et al, 2011(Manna et al, ) (1990 and Paengkoum and Paengkoum (2010) Pterocarpus marsupium Roxb. Ally and Kunjikutty (2003) Ally and Kunjikutty Hepatoprotective (Devipriya et al, 2007), (2003) hypoglycaemic (Dhanabal et al, 2006) Schleichera oleosa Prasad et al (1991) and Makkar et al (1990) Cytotoxic, radical-scavenging (Lour.)…”
Section: Resultsmentioning
confidence: 99%